Multibeam bathymetry and backscatter data analysis of pockmarks at Vestnesa Ridge off NW-Svalbard - Villaflor, Glennda Alina (UiT Norges arktiske universitet, 2014)
The Vestnesa Ridge is an elongated sediment drift situated at 79o N on the northwest Svalbard margin in the Fram Strait. It is one of the northernmost documented oceanic gas hydrate provinces. The narrow southeastern part of the ridge is characterized by pockmarks that line up along the apex of the crest. Some of these pockmarks are continuously venting gas while some are inactive. This study looks at changes in morphology of the pockmarks in relation to sedimentary processes, ocean currents and fluid flow mechanism, and their role in active fluid venting. Detailed bathymetry and backscatter data from different surveys in 2010, 2012 and 2013 are studied. Comparing the surfaces reveals relatively less sediment deposition in the pockmarks. The pockmarks exhibit an elongate shape and asymmetrical profiles, pointing to a strong influence by the WSC bottom currents. Backscatter data also reveal possible carbonate or gas hydrate deposits inside the pockmarks. These observations, along with apparent inactivity in some pockmarks, point to a possible scenario where carbonate or hydrate formation leads to self-sealing and eventual relocation of the gas vents through existing faults and fractures.